POLÍTICAS PÚBLICAS DE EDUCAÇÃO PROFISSIONAL E A INSERÇÃO DE EGRESSOS NO MERCADO DE TRABALHO | Public policies of professional education and the insertion of demands in the labor market (Trabalho & Educação, 2017)
This article presents the results of the research on the technical courses offered by the Federal Institute of Education, Science and Technology Goiano - Campus Morrinhos with the objective to analyze the process of professional insertion of the egresses of technical courses from the period of 2010 to 2014. The professional and technological education constitutes on a public policy focused on the integration between education and the demands of economic and social development at local and regional level. It is a research of an analytical nature, with a quantitative approach of the data collected. The information was obtained through the application of questionnaires to two groups of informants, being: egresses of technical courses with adhesion of 98, represented 44% and 11 employers from the Morrinhos - GO region. It was verified that 65% of the egresses are working, 30% work in their area of technical graduation, 86% have continued their studies and 53% declared that they are attending or have completed a higher education course related to technical formation. Employers were unanimous in stating that technical training represents a differential in the employee’s curriculum at the time of job selection and most of them are satisfied with the professional performance presented by contracted technicians. The development of this research indicated the need to deepen the institutional discussions about the curricular matrix of the technical courses; the areas of courses offered and greater integration between educational institutions and the productive sector, seeking the efficiency and feedback of educational policies focused on professional and technological education. ___Este artigo apresenta os resultados da pesquisa sobre os cursos técnicos ofertados pelo Instituto Federal de Educação, Ciência e Tecnologia Goiano – Campus Morrinhos, com o objetivo de analisar o processo de inserção profissional dos egressos de cursos técnicos concluintes no período de 2010 a 2014. A Educação Profissional e Tecnológica constitui-se em uma política pública voltada para a integração entre o ensino e as demandas de desenvolvimento econômico e social, em âmbito local e regional. Trata-se de pesquisa de natureza analítica, com abordagem quantitativa dos dados coletados. As informações foram obtidas por meio da aplicação de questionários a dois grupos de informantes, sendo eles: egressos de cursos técnicos com adesão de 98, representado 44%, e 11 empregadores da região de Morrinhos - GO. Verificou-se que 65% dos egressos estão trabalhando, 30% atuam em sua área de formação técnica, 86% deram continuidade aos estudos e 53% declararam estar frequentando ou terem concluído curso superior em área correlata à da formação técnica. Os empregadores foram unânimes ao afirmar que a formação técnica representa diferencial no currículo do trabalhador no momento da seleção de emprego, e a maioria deles está satisfeita com o desempenho profissional apresentado pelos técnicos contratados. O desenvolvimento desta pesquisa indicou a necessidade de aprofundamento nas discussões institucionais sobre a matriz curricular dos cursos técnicos, as áreas dos cursos ofertados e maior integração entre as instituições de ensino e o setor produtivo, buscando a eficiência e a retroalimentação das políticas educacionais voltadas para a Educação Profissional e Tecnológica.